2023
DOI: 10.3390/s23084116
|View full text |Cite
|
Sign up to set email alerts
|

A Sensing-Based Visualization Method for Representing Pressure Distribution in a Multi-Zone Building by Floor

Abstract: Airflow in a multi-zone building can be a major cause of pollutant transfer, excessive energy consumption, and occupants discomfort. The key to monitoring airflows and mitigating related problems is to obtain a comprehensive understanding of pressure relationships within the buildings. This study proposes a visualization method for representing pressure distribution within a multi-zone building by using a novel pressure-sensing system. The system consists of a Master device and a couple of Slave devices that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Environmental factors primarily include thermal buoyancy induced by an indoor/outdoor temperature difference and wind conditions. The effects of thermal buoyancy and wind on internal pressure difference have been 2 of 17 extensively studied [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], with various empirical prediction formulas proposed [14][15][16][17][18]. The studies showed that the vertical distribution of internal pressure difference due to thermal buoyancy is not only determined by the inside/outside temperature difference but also related to the distance from the neutral pressure layer (NPL) [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors primarily include thermal buoyancy induced by an indoor/outdoor temperature difference and wind conditions. The effects of thermal buoyancy and wind on internal pressure difference have been 2 of 17 extensively studied [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], with various empirical prediction formulas proposed [14][15][16][17][18]. The studies showed that the vertical distribution of internal pressure difference due to thermal buoyancy is not only determined by the inside/outside temperature difference but also related to the distance from the neutral pressure layer (NPL) [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, airtightness can play a significant role in building energy efficiency [11][12][13][14][15]. Recently, much attention has been paid to the importance of building airtightness [15][16][17].…”
Section: Introduction 1background and Objectivementioning
confidence: 99%